2018
DOI: 10.1158/1078-0432.ccr-17-2719
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers Increase Precision of the European Association of Urology Non–Muscle-Invasive Bladder Cancer Progression Risk Groups

Abstract: The European Association of Urology (EAU) guidelines for non-muscle-invasive bladder cancer (NMIBC) recommend risk stratification based on clinicopathologic parameters. Our aim was to investigate the added value of biomarkers to improve risk stratification of NMIBC. We prospectively included 1,239 patients in follow-up for NMIBC in six European countries. Fresh-frozen tumor samples were analyzed for , and methylation and , and mutation status. Cox regression analyses identified markers that were significantly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 22 publications
0
43
0
2
Order By: Relevance
“…Therefore, there may be some missing data, resulting in publication bias. Representative studies include UROMOL 2016 subtyping (33) and Van Kessel 2018 high-risk NMIBC subtyping (34). Thus, far, these two studies have the largest number of experimental cases in NMIBC molecular subtyping studies.…”
Section: Molecular Subtyping Of Nmibcmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there may be some missing data, resulting in publication bias. Representative studies include UROMOL 2016 subtyping (33) and Van Kessel 2018 high-risk NMIBC subtyping (34). Thus, far, these two studies have the largest number of experimental cases in NMIBC molecular subtyping studies.…”
Section: Molecular Subtyping Of Nmibcmentioning
confidence: 99%
“…Van Kessel et al (34) found that the methylation status of GATA2, TBX2, TBX3, and ZIC4 and mutations in FGFR3, TERT, PIK3CA, and RAS are correlated with the progression of NMIBC (41,42). Then, the research team detected and analyzed frozen tumor tissues of 1,239 patients with NMIBC from 6 European countries (276 patients were classified as low-risk, 273 as medium-risk and 555 as high-risk according to the EAU guidelines); ultimately, the high-risk NMIBCs were divided into three subtypes.…”
Section: High-risk Nmibc Subtypingmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐risk NMIBC patients are treated with intravesical Bacillus Calmette‐Guerin (BCG) or even radical cystectomy (RC). Predictors of increased risk include pathological stage T1, high pathological grade, molecular risk scores and an aggressive, Genomically Unstable or Basal/Squamous, molecular subtype . Recurrent as well as progressive disease has also been studied longitudinally in clinical and molecular studies .…”
Section: Introductionmentioning
confidence: 99%
“…The rapid proliferation of genetic and omic data in large cohort-based samples in the past decade have greatly advanced our understanding of the genetic architecture of omic profiles and the molecular mechanisms underpinning the genetic variation of human complex traits [1][2][3]. These advances include the identification of a large number of genetic variants associated with gene expression [4,5], DNA methylation [6,7], histone modification [8,9], and protein abundance [10,11]; the discovery of omic measures associated with complex traits [12,13]; the improved accuracy in predicting a trait using omic data [14,15]; and the prioritization of gene targets for complex traits by integrating genetic and omic data in large samples [3,13,[16][17][18]. These advances have also led to the development of software tools, focusing on a range of different aspects of omic data analysis.…”
Section: Introductionmentioning
confidence: 99%